Jenis-Jenis Kadal (Sub-Ordo Sauria) di Hutan Harapan Jambi - Kevin Origia; Wilson Novarino; Djong Hon Tjong (Jurnal Biologi Universitas Andalas, 2012)
Research of lizards (Sauria) in the Harapan Rainforest, Jambi was conducted from February to April 2012. The research was conducted using the direct capture and survey method. The result found of 14 species of lizards belongs to five families, which are Draco sumatrana, Aphaniotis fusca, and Bronchocela cristatella (Agamidae), Varanus salvator and Varanus sp. (Varanidae), Eutropis multifasciata and Eutropis macularia (Scincidae), Takydromus sexlineatus (Lacertidae), Cyrtodactylus sp., Hemidactylus platyurus, Hemidactylus frenatus, Hemidactylus sp., Gekko smithii and Gekko monarchus (Gekkonidae).Keywords: inventarisation, lizard, species, Harapan Rainforest, Jambi